Comprehensive evaluation of the educational impact and effectiveness of specialized study modules in cross-sectional anatomy: a study on student engagement and learning outcomes - Eren Ogut; Fatos Belgin Yildirim; Yesim Senol; A. Utku Senol (BMC Medical Education)
Abstract Background This study aimed to evaluate the effectiveness of Special Study Modules (SSMs) in Cross-Sectional Anatomy. These modules offer students the opportunity to develop their learning skills and foster specific academic interests. This study aimed to assess the satisfaction levels and learning outcomes of students who participated in the Cross-Sectional Anatomy SSMs, as determined by their feedback. Methods Data for this descriptive study were collected from student feedback at the beginning and end of the SSMs. A total of 100 undergraduate medical students provided feedback on the modules between 2018 and 2022. The student survey consisted of 11 questions, and feedback was obtained using an open-ended questionnaire. Results 74% of students emphasized the importance of these classes (p = 0.004).Teamwork was also significantly valued by 9% of students (p = 0.025). While 52% of students appreciated the module for presentation skills and clinical learning, the difference was not statistically significant. The module’s impact on career choice and communication with faculty was noted by 13% of the students (p = 0.057). Conclusions Cross-sectional anatomy SSMs were found to be valuable by students, enhancing their ability to identify anatomical structures in cross-sectional images and distinguish sections from different levels and regions. SSMs also promote greater proficiency in imaging techniques. Overall, these modules were effective in key educational domains, particularly in facilitating the integration of knowledge and fostering teamwork among participants.